Partial Reversal of Tissue Calcification and Extension of Life Span following Ammonium Nitrate Treatment of Klotho-Deficient Mice - Christina B. Leibrock; Martina Feger; Jakob Voelkl; Ursula Kohlhofer; Leticia Quintanilla-Martinez; Makoto Kuro-o; Florian Lang (Karger Publishers, 2016)
Background/Aims: Klotho is required for the inhibitory effect of FGF23 on 1,25(OH)2D3 formation and Klotho-hypomorphic mice (kl/kl) suffer from severe tissue calcification due to excessive 1,25(OH)2D3 formation with subsequent increase of Ca2+ and phosphate concentrations and stimulation of osteogenic signaling. The excessive tissue calcification dramatically accelerates aging and leads to premature death of the animals. Osteogenic signaling in those mice is disrupted by treatment with NH4Cl, which prevents tissue calcification and early death of kl/kl mice. The present study explored whether the beneficial effects of NH4Cl treatment could be mimicked by NH4NO3 treatment. Methods: The kl/kl mice had free access to tap water either without or with addition of NH4NO3 (0.28 M) starting with the mating of the parental generation. Calcification of trachea, lung, kidney, stomach, heart and vessels was visualized by histology with von Kossa staining. Plasma phosphate concentration was determined utilizing photometry, blood gas and electrolytes utilizing a blood Gas and Chemistry Analysis System and plasma 1,25(OH)2D3 concentration with ELISA. Results: In untreated kl/kl mice plasma 1,25(OH)2D3 and phosphate concentrations were elevated, and the mice suffered from marked calcification of all tissues analyzed. Untreated kl/kl mice further suffered from respiratory acidosis due to marked lung emphysema. NH4NO3-treatment decreased both, blood pCO2 and HCO3-, decreased calcification of trachea, lung, kidney, stomach, heart and vessels and increased the life span of kl/kl mice more than 1.7-fold (♂) or 1.6-fold (♀) without significantly affecting extracellular pH or plasma concentrations of 1,25(OH)2D3, Ca2+, phosphate, Na+, and K+. Conclusions: NH4NO3-treatment turns respiratory acidosis into metabolic acidosis and mitigates calcification thus leading to a substantial extension of kl/kl mice survival.